2020
DOI: 10.1103/physrevb.102.094312
|View full text |Cite
|
Sign up to set email alerts
|

Effective medium theory for a photonic pseudospin- 12 system

Abstract: Photonic pseudospin-1/2 systems, which exhibit Dirac cone dispersion at Brillouin zone corners in analogy to graphene, have been extensively studied in recent years.However, it is known that a linear band crossing of two bands cannot emerge at the center of Brillouin zone in a two-dimensional photonic system respecting time reversal symmetry. Using a square lattice of elliptical magneto-optical cylinders, we constructed an unpaired Dirac point at the Brillouin zone center as the intersection of the second and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…It is reasonable, as the PhC are composed of low-loss dielectric materials. It is interesting to point out the band dispersion of the PhC could be drastically deformed if there exists loss/gain [24,80,136,[151][152][153][154][155]175]. In 2015, Zhen et al experimentally demonstrated that in a photonic crystal slab the radiative loss-induced non-Hermitian perturbation can deform the Dirac-like cone into a 2D flat band enclosed by a ring of EPs [136].…”
Section: Non-hermitian Dirac-like Cones and Effective Medium Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reasonable, as the PhC are composed of low-loss dielectric materials. It is interesting to point out the band dispersion of the PhC could be drastically deformed if there exists loss/gain [24,80,136,[151][152][153][154][155]175]. In 2015, Zhen et al experimentally demonstrated that in a photonic crystal slab the radiative loss-induced non-Hermitian perturbation can deform the Dirac-like cone into a 2D flat band enclosed by a ring of EPs [136].…”
Section: Non-hermitian Dirac-like Cones and Effective Medium Descriptionmentioning
confidence: 99%
“…The PhC with a semi-Dirac cone behaves as an intriguing class of anisotropic ZIM with ε eff μ eff 0 along only one direction. The Dirac cone system has been extended from the original 2D to on-chip platform or the bound state in continuum (BIC) [22,[135][136][137][138][139][140][141][142][143][144][145][146][147] and three-dimension (3D) [148][149][150], and from the original Hermitian (lossless) to non-Hermitian (lossy or gain) ones [136,[151][152][153][154][155]. It was discovered that the Dirac degeneracy can be straightforwardly linked to exceptional points (EPs) through the introduction of non-Hermiticity, i.e., material loss, gain, or open boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, nodal lines in topological semimetals can even form some complicated configurations, including helices [12], rings [13][14][15][16][17][18][19], links [20,21], chains [22][23][24], gyroscopes [18,[25][26][27], nexus [28][29][30][31][32], knots [33][34][35][36], nets [37][38][39][40], etc. So far, more and more topological semimetals have been proposed theoretically and verified experimentally in the electronic [7][8], optical [11,19,24,32], and acoustic systems [23,[39][40][41]. As a result, a finer classification of topological phases is supported by band structure of semimetals.…”
Section: Introductionmentioning
confidence: 99%
“…In the momentum k-space, topological semimetals possess robust nodal areas between conduction and valence bands. In particular, the co-dimension of nodal points [7][8][9][10][11], nodal lines and nodal surfaces [42][43][44] is 3, 2 and 1 respectively, which corresponding to the degrees of freedom of parameters that tuned to encounter a band degeneracy [45]. Interestingly, nodal lines in topological semimetals can even form some complicated configurations, including helices [12], rings [13][14][15][16][17][18][19], links [20,21], chains [22][23][24], gyroscopes [18,[25][26][27], nexus [28][29][30][31][32], knots [33][34][35][36], nets [37][38][39][40], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation